Imagens de arquivo, cenas desconhecidas: um estudo sobre Bibliotecários, Jornalistas, rede de relações e práticas informacionais em arquivos de Telejornalismo - Delfim Afonso Junior (2008)
In the context of new aspects of the informations organization, this thesis focuses on the informational relations and practices of professionals that act in the documentation departments of TV stations. Through actor-network theory, with an empirical research of ethnographic type at Globo Network, in Belo Horizonte and Rio de Janeiro, we can say that the insertion, performance and intervention of librarians stand out on the newscast production and in the news network construction. The point of this research is to bring the idea that the journalistic production is made by heterogeneous and plural agents with journalists and librarians among them. The intention is to show the mixture in the production and the organization of information in the production of the newscast programs as a new fact, where there is a new actor: the multidisciplinary and interdisciplinary staff. This mixture in the production and the organization of information in the newscast, with the urgency of the multifunctional staff and its multiple actors was not studied yet in the respective and specific informational practices and in the implications of the action takings, in a direct way, of the organization of information in thenewscast production network. According to the intentions of this study the actor-network theory (Bruno Latour and Bernd Frohmann) was put as the main point and it privileges the investigation of micro-processes from which the production of information emerges and is produced, in thiscase becoming a result of the emphasis in the association of journalists and librarians for the newscast production. Regarding the methodology, the empirical research was made using the participants observation practice, the gathering of testimonials, documents and interviews. At thebackstage of TV network documentation departments a species of estimation center to the production, organization and information research in verbal, oral and audiovisual documents the librarians, journalists, technologies, indexing languages and TV technicians mingle, in a cooperative labour, in displacements, places and unstable and contradictory positioning. To achieve its goal, the research focuses the exchange and negotiations of ideas, values, bonds, point of view and knowledge of librarians and journalists that lead to the confluence of the production and organization of information in the TV news network. Because of the material, intellectual, technological and discursive practices these professionals have to manage in the relationnetwork context with the challenge of making information cross as a commercial product to the condition of social memory artifact.